Nicotine and sympathetic neurotransmission - Haass, Markus; Kübler, Wolfgang (Cardiovascular drugs and therapy, 1997)
Nicotine increases heart rate, myocardial contractility, and blood pressure. These nicotine-induced cardiovascular effects are mainly due to stimulation of sympathetic neurotransmission, as nicotine stimulates catecholamine release by an activation of nicotinic acetylcholine receptors localized on peripheral postganglionic sympathetic nerve endings and the adrenal medulla. The nicotinic acetylcholine receptor is a ligand-gated cation channel with a pentameric structure and a central pore with a cation gate, which is essential for ion selectivity and permeability. Binding of nicotine to its extracellular binding site leads to a conformational change of the central pore, which results in the influx of sodium and calcium ions. The resulting depolarization of the sympathetic nerve ending stimulates calcium influx through voltage-dependent N-type calcium channels, which triggers the nicotine-evoked exocytotic catecholamine release. In the isolated perfused guinea-pig heart, cardiac energy depletion sensitizes cardiac sympathetic nerves to the norepinephrine-releasing effect of nicotine, as indicated by a leftward shift of the concentration-response curve, a potentiation of maximum transmitter release, and a delay of the tachyphylaxis of nicotine-evoked catecholamine release. This sensitization was also shown to occur in the human heart under in vitro conditions. Through the intracardiac release of norepinephrine, nicotine induces a beta-adrenoceptormediated increase in heart rate and contractility, and an alpha-adrenoceptor-mediated increase in coronary vasomotor tone. The resulting simultaneous increase in oxygen demand and coronary resistance has a detrimental effect on the oxygen balance of the heart, especially in patients with coronary artery disease. Sensitization of the ischemic heart to the norepinephrine-releasing effect of nicotine may be a trigger for acute cardiovascular events in humans, such as acute myocardial infarction and/or life-threatening ventricular tachyarrhythmias.
Gesehen am 12.05.2025